Why Has the Share of Two-Child Families Stopped Growing? Trends in Education-Specific Parity Distribution in Low-Fertility Countries - Zuzanna Brzozowska; Kryštof Zeman; Éva Beaujouan (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2017)
During the last four decades, the two-child family ideal has become nearly universal across the low-fertility countries. The proportion of families with two children, which was growing during the baby boom, stopped increasing in the late 1940s and early 1950s birth cohorts, remaining far below the number of people reporting two as their ideal family size. This paper examines how changes in the share of two-child families were linked to trends in the transitions to first, second and third birth. We analyse how the relationship varied over time across countries and education levels using census and large-scale survey data for women born between 1936 and 1970 in 12 European countries, Australia, New Zealand and the United States. The results suggest that in most countries the changes in the share of two-child families were closely linked to the progression to third birth. Increasing childlessness also suppressed the number of two-child families in Western Germany and English-speaking countries. Changes in the transition to second birth played a nonnegligible role in Southern Europe, English-speaking countries and, except among the loweducated, in Central-Eastern Europe.
Keywords: 300; Parity distribution; parity progression ratios; fertility and education; fertility trends